Deep venous thrombosis of the inferior limbs - Matteucci, Pablo; Lerena, Ana; Ricciardi, Norma (Cirugía del Uruguay, 1984)
The Hospital de Clínicas experience. Fifty cases of deep venous thrombosis of the inferior limb, observed at the Montevideo's Hospital de Clinicas, are presented. The benefils of !he medica! treatmenl with anticoagulant therapy, done in 94% of the cases is pointed out.